Penghulu Sebagai Terapis: Studi Etnografi Tentang Praktik Konseling Informal di KUA Kecamatan Medan Tembung (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the role of the head as a therapist in informal counseling practice at the Religious Affairs Office (KUA) of Medan Tembung District. Penghulu not only carries out administrative functions as marriage registrars, but also acts as a religious figure who provides psychosocial and spiritual assistance to the community. In practice, the penghulu is often the first referral place for married couples, prospective brides, and families who face problems in relationships, communication, and domestic conflicts. This study aims to describe the forms of informal counseling carried out by the penghulu and understand the meaning of the practice in the social and cultural context of the local community, including the religious values, customs, and community norms that underlie it. This study uses a qualitative approach with ethnographic methods through participant observation and in-depth interviews. This study concludes that informal counseling practices by the head have an important contribution in fostering family resilience and preventing domestic conflicts. These findings confirm that the role of the head in KUA is not only administrative, but also social, cultural, and therapeutic in people's lives.